2023
DOI: 10.1177/00048674231160986
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes of Aboriginal women with mental health disorders

Abstract: Objective: Maternal mental disorders have been associated with adverse perinatal outcomes such as low birthweight and preterm birth, although these links have been examined rarely among Australian Aboriginal populations. We aimed to evaluate the association between maternal mental disorders and adverse perinatal outcomes among Aboriginal births. Methods: We used whole population-based linked data to conduct a retrospective cohort study ( N = 38,592) using all Western Australia singleton Aboriginal births (1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“… 36 , 37 Prior evidence regarding the association between maternal MHrH and SB is inconsistent. 13 , 34 Our study finding substantiates those findings that reported association between maternal MHrH and SB. Infant birth length is the strongest predictor of linear growth status in early childhood 38 where the link between maternal mental health condition and birth length has never been explored.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“… 36 , 37 Prior evidence regarding the association between maternal MHrH and SB is inconsistent. 13 , 34 Our study finding substantiates those findings that reported association between maternal MHrH and SB. Infant birth length is the strongest predictor of linear growth status in early childhood 38 where the link between maternal mental health condition and birth length has never been explored.…”
Section: Discussionsupporting
confidence: 91%
“…Our study replicates previous findings that maternal MHrH before or during pregnancy increases the risk of PTB and LBW in both non-Aboriginal and Aboriginal women. 5 , 6 , 13 , 34 We propose four potential pathways to explain this link: i) MHrH effects are mediated by obstetric complications leading to adverse birth outcomes; ii) Women with psychiatric diagnoses are more likely to engage in behaviours such as smoking and alcohol consumption during pregnancy, which can lead to poor fetal growth and subsequent adverse birth outcomes; iii) Biological and hormonal pathways involving psychiatric symptoms lead to elevated cortisol production or plasminogen activator inhibitor 1 (PAI-1), which can adversely alter the intrauterine environment and contribute to adverse birth outcomes 35 ; and iv) mental health disorders affects maternal health service uptake including ANC—our study demonstrated that ANC service attendance mediated most of the paths from pre-pregnancy maternal MHrH to adverse birth outcomes —and attending at least eight ANC service demonstrated to prevent a significant number of adverse birth outcomes. 36 , 37 Prior evidence regarding the association between maternal MHrH and SB is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation